TCP HACK: TCP Header Checksum Option to Improve Performance Over Lossy Links - BALAN, Rajesh Krishna (Institutional Knowledge at Singapore Management University, 2001)
Wireless networks have become increasingly common and an increasing number of devices are communicating with each other over lossy links. Unfortunately, TCP performs poorly over lossy links as it is unable to differentiate the loss due to packet corruption from that due to congestion. We present an extension to TCP which enables TCP to distinguish packet corruption from congestion in lossy environments resulting in improved performance. We refer to this extension as the HeAder ChecKsum option (HACK). We implemented our algorithm in the Linux kernel and performed various tests to determine its effectiveness. Our results have shown that HACK performs substantially better than both SACK and NewReno in cases where burst corruptions are frequent. We also found that HACK can co-exist very nicely with SACK and performs even better with SACK enabled